GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 512 species occurrences available in GBIF matching the query: TaxonKey: Eryngium pandanifolium Cham. & Schltdl.. The dataset includes 512 records from 62 constituent datasets: 6 records from OEH Atlas of NSW Wildlife. 1 records from University of Vienna, Institute for Botany - Herbarium WU. 2 records from IAC - Herbário do Instituto Agronômico de Campinas. 31 records from Naturalis Biodiversity Center (NL) - Botany. 14 records from ICN - Herbário do Instituto de Ciências Naturais. 2 records from CESJ - Herbário Leopoldo Krieger. 2 records from OUPR - Herbário "Professor José Badini". 15 records from MBM - Herbário do Museu Botânico Municipal. 5 records from RB - Rio de Janeiro Botanical Garden Herbarium Collection. 15 records from Australia's Virtual Herbarium. 1 records from Fundación Biodiversidad, Real Jardín Botánico (CSIC): Anthos. Sistema de Información de las plantas de España. 1 records from Natural History Museum Maastricht (NL) - Herbarium. 10 records from HUCS - Herbário da Universidade de Caxias do Sul. 1 records from HPBR - Herbário Padre Balduino Rambo. 4 records from LUSC - Herbário de Lages da Universidade do Estado de Santa Catarina. 2 records from EFC - Herbário Escola de Florestas Curitiba. 2 records from FUEL - Herbário da Universidade Estadual de Londrina. 2 records from Royal Botanic Garden Edinburgh Living Plant Collections (E). 45 records from Tropicos Specimen Data. 5 records from Natural History Museum (London) Collection Specimens. 17 records from Flora-On: occurrence data of the flora of mainland Portugal. 2 records from Karl Franzens University of Graz, Insitute for Botany - Herbarium GZU. 2 records from Australian National Herbarium (CANB). 3 records from Colección de plantas vasculares del herbario de la Universitat de València (VAL).. 1 records from Herbario de Plantas Vasculares de la Universidad de Salamanca: SALA. 5 records from Real Jardín Botánico (Madrid), Vascular Plant Herbarium (MA). 1 records from Universidad del País Vasco/EHU, Bilbao: Herbario BIO. 1 records from Herbario de la Universidad de Sevilla. 4 records from Auckland Museum Botany Collection. 8 records from NSW herbarium collection. 2 records from Staatliches Museum für Naturkunde Stuttgart, Herbarium. 4 records from United States National Plant Germplasm System Collection. 2 records from Field Museum of Natural History (Botany) Seed Plant Collection. 6 records from Colección de plantas vasculares de Brasil del Herbario "Jaime Andrés Rodríguez". LEB-Brasil. 1 records from Biological and palaeontological collection and observation data MNHNL. 1 records from VIT Herbarium - Vascular Plants (The Natural History Museum of Alava). 4 records from HVAT - Herbário do Vale do Taquari. 1 records from Registros biológicos en áreas protegidas obtenidos de documentos impresos. 68 records from The vascular plants collection (P) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 2 records from FURB - Herbário Dr. Roberto Miguel Klein. 4 records from Royal Botanic Garden Edinburgh Herbarium (E). 10 records from HAS - Herbário Alarich Rudolf Holger Schultz. 1 records from University of British Columbia Botanical Garden Collections (UBCBG). 1 records from Herbarium specimens of Université de Montpellier 2, Institut de Botanique (MPU)). 8 records from ESA - Herbário da Escola Superior de Agricultura Luiz de Queiroz. 2 records from R - Herbário do Museu Nacional. 18 records from Royal Botanic Gardens, Kew - Herbarium Specimens. 5 records from MPUC - Herbário do Museu da Pontifícia Universidade Católica do Rio Grande do Sul. 2 records from BHCB - Herbário da Universidade Federal de Minas Gerais. 16 records from The New York Botanical Garden Herbarium (NY) - Vascular Plant Collection. 7 records from UB - Herbário da Universidade de Brasília. 3 records from HCF - Herbário da Universidade Tecnológica Federal do Paraná Campus Campo Mourão. 8 records from Allan Herbarium (CHR). 4 records from SysTax - Botanical Gardens. 1 records from Colección Nacional de Actuopalinología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 14 records from CGMS - Herbário da Fundação Universidade Federal de Mato Grosso do Sul. 1 records from IPA - Herbário - IPA Dárdano de Andrade Lima. 35 records from Instituto de Botánica Darwinion. 2 records from CPAP - Herbário CPAP. 1 records from BHZB - Herbário do Jardim Botânico da Fundação Zoo-Botânica de Belo Horizonte. 51 records from PACA-AGP - Herbarium Anchieta. 17 records from Sightings Map of Invasive Plants in Portugal.
Keywords: GBIF; biodiversity; species occurrences